Treatment Challenges in Pediatric Stroke Patients. (5th December 2010) - Yılmaz, A.; Teber, S.; Bektaş, Ö; Akar, N.; Uysal, L. Z.; Aksoy, E.; Deda, G.
Abstract : Aim . In this study we presented our experience of 18 years on the etiology, risk factors, prophylactic and acute treatment, the effect of treatment to recurrence rate of patients with stroke. Methods . The population included 108 patients who had been treated for stroke at Pediatric Neurology Department of Ankara University with the diagnosis of arterial ischemic stroke and sinovenous thrombosis between January 1992 and August 2010. Forty-one girls (38%) and 67 boys (62%) with mean symptom age3.1 ± 4.04 years, (0–18 years old) were followed up with a mean period of4.9 ± 3.78 years (0–17 years). Results . 30 patients had no risk factors, 34 patients had only one risk factor and 44 patients had multiple risk factors. Recurrence was seen in three patients. There was no any statistical correlation between the recurrence of stroke and the existence of risk factors (P = .961 ). Seventeen patients received prophylactic treatment; 2 of them without any risk factors, 3 had one risk factor, 12 patients, who constituted the majority of our patients, had multiple risk factors (P = .024 ). Conclusion . With this study we showed that the right prophylaxis for right patients reduces the rate of recurrence.